Education: 11. Artistic Education, A Promoter for the Development of School Creativity from the Intercultural Perspective - Paşca Eugenia Maria (Sciendo, 2018)
The main aims of artistic education are almost similar in all European countries. Almost all countries mention "artistic skills, knowledge and understanding", "critical appreciation", "cultural heritage", "individual expression/identity", "cultural diversity" and "creativity" as objectives. However, "arts and permanent learning/interest" are mentioned only in 15 curricula. The various initiatives and recommendations for the development of artistic and cultural education in European countries are based on information on the establishment of national organizations and networks to promote artistic education and the development of partnerships between schools, artistic/cultural organizations and artists. Cultural identity as well as the development of creativity are a priority through such approaches.